Effect of Godelieve Denys-Struyf (GDS) muscle and articulation chain treatment on clinical variables of patients with chronic low back pain and lumbar disc degeneration: a pilot feasibility randomized controlled trial - Sidsel Lombardo; Gunvor Hilde; Milada Cvancarova Småstuen; Margreth Grotle (Pilot and Feasibility Studies, 2023)
Abstract Background Patients with chronic low back pain (LBP) and lumbar disc degeneration are recommended to try out nonsurgical treatment options before surgery. There is need for good nonsurgical alternatives that can be adapted to the patient’s needs and level of function. The aim of this pilot trial was to test study feasibility of a future full randomized controlled trial (RCT) evaluating the feasibility and benefit of the physiotherapy-based Godelieve Denys-Struyf (GDS) muscle and articulation chain treatment for patients with chronic LBP and lumbar disc degeneration referred to surgical assessment in a hospital outpatient clinic. Methods This study is a single-center, two-arm, single-blinded, pilot RCT conducted in a regional hospital in Norway. Patients of age 35–75 years with chronic (> 3 months) LBP and degenerative lumbar disc(s) verified by imaging were included. They filled in a baseline questionnaire prior to randomization, including the Oswestry Disability Index (ODI), numerical rating scale for pain in back and pain in leg, and the EuroQoL 5L. Patients in the control group were free to use treatment as usual. Patients in the intervention group received 8 sessions over a period of 10 to 14 weeks of GDS muscle and articulation chain treatment. Results The recruitment rate was slow, approximately 3/4th of the referred patients met the inclusion criteria, but majority of eligible participants (94%) were willing to participate. A total of 30 patients were randomized into the two groups. The randomization led to skewed distribution of radiating leg pain in the two groups. All participants except one (97%) completed 4 months follow-up. No serious adverse events attributable to the trial treatments were reported. The Oswestry Disability Index (ODI) and leg pain intensity scale were both suitable as primary outcomes in a full trial. The mean change in the ODI score was 8.7 (SD 16.1) points in the GDS arm, whereas there was a minor deterioration in the ODI scores of −3.7 (7.5) points in the control arm. A sample size calculation based on the ODI scores resulted in a number needed to treat of 3. Conclusions A future full RCT is feasible and would provide evidence about the effectiveness of a GDS treatment for patients with chronic LBP and lumbar disc degeneration. Trial registration ClinicalTrials.gov ID: 910193.